Analisis Faktor-Faktor Yang Mempengaruhi Kesejahteraan Lansia di Kecamatan Mengwi, Kabupaten Badung - Kartini, Putu Yunny Lestari; Kartika, I Nengah (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2020)
One indicator that reflects the success of development is an increase in the population's life expectancy, which also has an impact on increasing the number of elderly people. The purpose of the study is to analyze the effect of education level, employment status, income, marital status, and simultaneous and partial health access to the welfare of the elderly in Mengwi, Badung. The sample size of 100 seniors from a total of 13,082. Data collection is done through observation, structured interviews and in-depth interviews, analyzed by multiple linear regression. Based on the results, Education Level, Employment Status, Income, Marital Status, and Health Access have a significant and simultaneous influence on the well-being of the elderly. This means that the higher the Education Level, Employment Status, Income, Marital Status, and Health Access of the elderly, the welfare of the elderly in Mengwi, Badung will increase.